Recognition of infections in elderly emergency patients - Hortmann, M.; Singler, Katrin; Geier, F.; Christ, M. (Zeitschrift für Gerontologie und Geriatrie, 2015)
Elderly patients represent an increasing population in the emergency department (ED) and physicians often have to deal with multimorbidity and complexity. Infections are one of the major reasons for ED presentations of older patients and the main cause of mortality; however, infections are often difficult to diagnose in older patients.This article provides a review of important indicators for infections, diagnostic tools and limitations in elderly patients.A literature search was carried out using PubMed in the period 1990-2015 and in addition own published data are presented.Infections in the elderly are difficult to assess in the emergency department due to atypical symptoms. Even subtle changes need to be recognized. For the diagnosis of infections in older ED patients unspecific symptoms, vital parameters, laboratory parameters, including C-reactive protein (CRP) and procalcitonin levels, cognitive function and functionality of the patient need to be taken into account.
EVALuna2:10577